Placebo Effects in Therapeutic Outcomes - p. Horin, Adam; M. Lee, Kent; Colloca, Luana (Current Clinical Pharmacology, 2014)
The goal of this review is to address the medical implications of placebos and placebo effects in future medical practice. The applications of placebos have become increasingly relevant due to a recent abundance of clinical research that has been conducted on the mechanisms under which a placebo response is formed. With current research on placebo, the thoughts of using placebo effects as an effective form of co-treatment for patients with disorders such as pain, depression or Parkinson's disease might become a feasible proposition. This review focuses on crucial studies that have been done in this area of research with regard to the physiological and psychological mechanisms that are associated with the formation of a placebo effect, as well as emphasizing the patient-clinician relationship and the importance of this relationship for a successful treatment regimen.
Keywords: conditioning